Power Distance Orientation Dilutes the Effect of Abusive Supervision on Workplace Deviance. (November 2017) - Hussain, Imran; Sia, Surendra Kumar
Deviant behaviour in workplace has become an issue of concern in today's corporate world. As a result of hard costs, the negative impact of deviant behaviour leaves a devastating effect on overall productivity and performance of the organization. We assumed that abusive supervision will be positively related to employee's interpersonal and organizational deviance. Moreover, we also hypothesized that this relationship of abusive supervision with both interpersonal and organizational deviance will be moderated by power distance. We verified the formulated hypotheses using data collected from 256 mid-level managerial employees working in IT and software companies based in Delhi (India). Data analysis was done through confirmatory factor analysis (CFA) and moderated regression analysis. Results reveal significant and positive contribution of abusive supervision towards employee's workplace deviance. Power distance orientation significantly moderates the relationship between abusive supervision and employee's interpersonal and organizational deviance. The implications for the result obtained are discussed.